Peranan Gaya Hidup, Citra Merk dan Kualitas Produk dalam Keputusan Pembelian Smartphone Samsung di Kota Salatiga - Andri Setyawan; Mada Adi Wibowo; Budi Riyanti (STIE AUB Surakarta, 2026)
This study examines the influence of lifestyle, brand image, and product quality on purchasing decisions for Samsung smartphones in Salatiga City. Based on a sample of 100 respondents and using multiple linear regression analysis, the t-test (partial) results indicate that lifestyle and product quality have a significant influence on purchasing decisions, whereas brand image does not have a significant effect on Samsung smartphone purchasing decisions in Salatiga City. A strong brand like Samsung does not necessarily drive consumer purchases if it is not accompanied by other factors deemed more important by consumers—such as the product's alignment with their lifestyle, usage needs, and the quality of the product offered.